Priority setting for nutrition research in individuals with spinal cord injury: A protocol for Delphi study among health professionals. - Marija Glisic; Shashivadan P Hirani; Hanne Bjørg Slettahjell; Willemijn Faber; Yannis Dionyssiotis; Alastair Forbes; Anthony Twist; Emil Moga; Jackie McRae; Firas Sarhan; Sharon Leigh; Samford Wong (PLoS ONE)
Study design A protocol for Delphi Consensus Study. Objectives To identify a top ten list of priorities for future nutrition research in individuals with spinal cord injury (SCI). Setting The International Spinal Cord Society (ISCoS) Nutrition Specialist Interest Group (SIG) priority setting partnership was established in 2024 to conduct this international Delphi study through online surveys and a hybrid meeting. Methods The study involves THREE key stages: topic generation, priority ranking, and consensus building. In phase 1, participants will generate potential research topics via an online survey. Phase 2 involves ranking the top 10 research priorities on a 9-point Likert scale. Phase 3 consists of a consensus meeting where stakeholders will engage in discussions and vote on the final priorities using interactive tools. For Phases 1 and 2, both ISCoS Nutrition SIG members and their professional contacts will be invited to participate, ensuring a diverse pool of expertise. Phase 3 will be limited to Nutrition SIG members to facilitate focused decision-making. Data will be collected through secure Qualtrics surveys and analysed using descriptive statistics in STATA or SPSS. The study adheres to the Conducting and Reporting of DElphi Studies (CREDES) recommendations and employs rigorous data management practices compliant with City St George's, University of London standards. Ethics and dissemination Ethics approval has been granted (ref: ETH2425-0192, Health Services Research & Management Proportionate Review Committee, City St George's, University of London). The findings will be disseminated through ISCoS website, professional conferences and a peer-reviewed journal.